TEORI-TEORI PENGEMBANGAN SUMBER DAYA MANUSIA PENDIDIKAN ISLAM DAN TANTANGAN MODERN - Sera Yuliantini; Nurlisa (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the theories of human resource development (HRD) in Islamic education and to identify the modern challenges it faces. Employing a qualitative approach and utilizing the method of library research, the findings of this study highlight that HRD in Islamic education is a form of human investment—a strategic process aimed at shaping Muslim individuals who are intellectually, morally, and spiritually competent. The study explores various theoretical concepts and discusses learning outcomes across three essential domains: cognitive, affective, and psychomotor. Islamic education is not solely focused on academic achievement; it also emphasizes the holistic development of human potential, including the intellect (‘aql), heart (qalb), soul (ruh), self (nafs), and natural disposition (fitrah). The study also identifies a range of modern challenges—both internal and external—faced by Islamic education today, including advances in science and technology, democratization, moral decline, educational inequality, modernization and secularization, and multiculturalism.